DEVELOPMENT OF DILEMMA-STEAM-BASEDPHYSICSLEARNING VIDEOS ON RENEWABLE ENERGYMATERIAL: PENGEMBANGAN VIDEO PEMBELAJARAN FISIKA BERBASIS DILEMA-STEAM PADA MATERI ENERGI TERBARUKAN - Raden Roro Sekar Ayu Nur Fadhila; Hadi Nasbey; Mutia Delina (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This research aims to develop a video with Dilemma-STEAMlearningmodel onRenewable Energy material that is feasible to be used as teaching material for class Xhighschool physics. Dilemma-STEAM-based Learning Video is a physics learning videobased on the dilemma stories and STEAM-pjbl learning model. This learning model aimstoengage students in discussion and analysis of dilemma stories related to renewable energy. The method used is Research and Development (R&D) with the Analysis, Design, Development, Implementation & Evaluation (ADDIE) research model. Based on theresultsof an analysis of 54 students at a high school in East Jakarta regarding teaching materialsat school. It was found that 93% of students need learning videos to support physics teachingmaterials at school. The final product of this research is a learning video design that canbeaccessed easily by students.